Evaluation of the red seaweed Mazzaella japonica as a feed additive for beef cattle - Terry, Stephanie A.; Coates, Trevor; Gruninger, Robert; Abbott, D. Wade; Beauchemin, Karen A. (Frontiers in Animal Science, 2023)
Supplementing ruminant diets with macroalgae is gaining interest globally because bromoform-containing seaweeds (e.g., Asparagopsis spp.) have been shown to be highly effective enteric methane (CH4) inhibitors. Some alternative seaweeds decrease in vitro CH4 production, but few have been evaluated in animals. This study examined the effects of including the red seaweed Mazzaella japonica in the diet of beef cattle on dry matter intake (DMI), rumen fermentation, digestibility, nitrogen (N) utilization, and enteric CH4 production. Six ruminally cannulated, mature beef heifers (824 ± 47.1 kg) were used in a double 3 × 3 Latin square with 35-d periods. The basal diet consisted of 52% barley silage, 44% barley straw, and 4% vitamin and mineral supplement [dry matter (DM) basis]. The treatments were (DM basis): 0% (control), 1%, and 2% M. japonica. The DMI increased quadratically (P = 0.025) with the inclusion of M. japonica, such that the DMI of heifers consuming 1% was greater (P < 0.05) than that of control heifers. The apparent total-tract digestibility of DM decreased linearly (P = 0.002) with the inclusion of M. japonica, but there were no treatment differences in the digestibility of organic matter, crude protein (CP), neutral detergent fiber, or starch. The level of M. japonica linearly (P < 0.001) increased the N intake of the heifers. Fecal N excretion linearly increased (P = 0.020) with M. japonica, but there were no differences in total urinary N excretion, N fractions (allantoin, uric acid), total purine derivatives, microbial purine derivatives absorbed, microbial N flow, or retained N. There were no treatment effects on rumen pH or total volatile fatty acids (VFAs); however, adding M. japonica to the diet quadratically (P = 0.023) decreased the proportion of acetate, whereas 1% inclusion decreased the acetate proportion. Methane production (g/day) decreased quadratically (P = 0.037), such that the heifers receiving 2% M. japonica produced 9.2% less CH4 than control animals; however, CH4 yield (g/kg DMI) did not differ among treatments. We conclude that supplementing a forage-based diet with up to 2% M. japonica failed to lower the enteric CH4 yield of beef heifers. M. japonica can be used in diets to help meet the CP requirements of cattle, but inclusion rates may be limited by high inorganic matter proportions. When comprising up to 2% of the diet, M. japonica cannot be recommended as a CH4 inhibitor for beef cattle fed on high-forage diets.